Nutritional assessment and dietary intervention among survivors of childhood cancer: current landscape and a look to the future - Feit, Talia; Beals, Elizabeth; Dandekar, Smita; Kadan-Lottick, Nina; Joffe, Lenat (Frontiers in Nutrition, 2024)
Over 85% of childhood cancer patients become long-term survivors. Still, cancer and its therapies are associated with a myriad of long-term complications such that childhood cancer survivors (CCS) endure excess disease burden, morbidity, and mortality throughout their lifetimes. Existing literature suggests that CCS maintain poor dietary intake and nutritional status. Thus, as childhood cancer cure rates continue to improve, the role of diet and nutrition in mitigating many of the most common adverse long-term health outcomes among CCS has gained significant interest. Herein we review present an in-depth review of existing scientific knowledge literature regarding evaluating dietary intake and nutrition status among CCS and its impact on treatment-related health complications; as well as contemporary intervention strategies aimed at overcoming distinctive barriers and improving deleterious lifestyle behaviors in this population. We summarize the Ppatient-centered, clinical, and systemic factors act as barriers to the conducting timely , comprehensive conduct of comprehensive dietary/nutritional assessments and providing provision of tailored, risk-based recommendations. We highlightThis Mini Review discusses the current state of the science, persisting research gaps, and opportunities for advancement of assessment and intervention strategies to address the unique needs of this heterogeneous, at-risk group of CCS.